Medicago truncatula Ferroportin2 mediates iron import into nodule symbiosomes - Escudero, Viviana; Abreu, Isidro; Tejada Jiménez, Manuel; Rosa Núñez, Elena; Quintana, Julia; Prieto, Rosa Isabel; Larue, Camille; Wen, Jiangqi; Villanova, Julie; Mysore, Kirankumar S.; Argüello, José M.; Castillo Michel, Hiram; et al. (My University, 2024)
Iron is an essential cofactor for symbiotic nitrogen fixation, required by many of the enzymes involved, including signal transduction proteins, O2 homeostasis systems, and nitro genase itself. Consequently, host plants have developed a transport network to deliver essen tial iron to nitrogen-fixing nodule cells. Ferroportin family members in model legume Medicago truncatula were identified and their expression was determined. Yeast complementation assays, immunolocalization, characteri zation of a tnt1 insertional mutant line, and synchrotron-based X-ray fluorescence assays were carried out in the nodule-specific M. truncatula ferroportin Medicago truncatula nodule-specific gene Ferroportin2 (MtFPN2) is an iron-efflux protein. MtFPN2 is located in intracellular membranes in the nodule vasculature and in inner nodule tissues, as well as in the symbiosome membranes in the interzone and early-fixation zone of the nodules. Loss-of-function of MtFPN2 alters iron distribution and speciation in nodules, reducing nitrogenase activity and biomass production. Using promoters with different tissular activity to drive MtFPN2 expression in MtFPN2 mutants, we determined that expression in the inner nodule tissues is sufficient to restore the phenotype, while confining MtFPN2 expression to the vasculature did not improve the mutant phenotype. These data indicate that MtFPN2 plays a primary role in iron delivery to nitrogen-fixing bac teroids in M. truncatula nodules.